A comparison of risk factors as predictors of cardiovascular and non‐cardiovascular mortality in the elderly people – relevance of N‐terminal pro‐B‐type natriuretic peptide and low systolic blood pressure. Issue 11 (24th October 2013) - Muscari, A.; Bianchi, G.; Forti, P.; Giansante, C.; Giovagnoli, M.; Magalotti, D.; Pandolfi, P.; Perlangeli, V.; Zorzi, V.; Zoli, M.; ,
Summary: Background: Many risk factors are known to predict ischaemic events and mortality in the elderly people, but their ranking of importance remains uncertain. This study was designed to identify and compare the main predictors of total mortality (TM), cardiovascular mortality (CVM) and non‐cardiovascular mortality (NCVM) in older adults. Methods: Nine hundred and seventy‐nine community resident adults aged ≥ 65 years, free of previous heart failure and cardiovascular events, participated in the study. The univariate and multivariate (Cox regression) relationships of baseline cardiovascular risk factors, treatments and laboratory data with TM, CVM and NCVM were assessed after a median follow up of 6.7 years. Results: Overall, there were 104 deaths (30 because of CVM and 74 to NCVM). In multivariate analysis, the following factors remained independently associated with mortality: NT pro‐B‐type natriuretic peptide (NT‐proBNP) upper quintile (≥ 237 pg/ml for men, ≥ 280 pg/ml for women): hazard ratio (HR) vs. the rest of the population (95% confidence interval) 2.34 (1.52–3.60), p < 0.001 for TM; HR 5.41 (2.32–12.65), p < 0.001 for CVM; systolic blood pressure lower quintile (≤ 130 mmHg): HR 3.06 (1.80–5.21), p < 0.001 for NCVM; diabetes: HR 2.46 (1.29–4.72), p = 0.007 for NCVM; erythrocyte sedimentation rate (ESR) upper decile (≥ 41 mm/h): HR 2.33 (1.16–4.69), p = 0.02 for NCVM; platelet count lower quintile (≤ 177 × 10 9 /l): HR 2.09 (1.20–3.64), p = 0.009 for NCVM; ever‐smoker status: HR 2.08 (1.23–3.52), p = 0.007 for NCVM. Conclusions: In elderly community dwellers, NT‐proBNP was the strongest predictor of TM and CVM, while especially low systolic blood pressure, together with diabetes, ESR, reduced platelet count and ever‐smoker status, were the main predictors of NCVM.